Habitual nappers and non-nappers differ in circadian rhythms of LIPE expression in abdominal adipose tissue explants - Zambrano, Carolina; Kulyté, Agné; Luján, Juán; Rivero-Gutierrez, Belén; Sánchez de Medina, Fermín; Martínez-Augustin, Olga; Ryden, Mikael; Scheer, Frank A. J. L.; Garaulet, Marta (Frontiers in Endocrinology, 2023)
Background and purpose Napping is a widespread practice worldwide and has in recent years been linked to increased abdominal adiposity. Lipase E or LIPE encodes the protein hormone-sensitive lipase (HSL), an enzyme that plays an important role in lipid mobilization and exhibits a circadian expression rhythm in human adipose tissue. We hypothesized that habitual napping may impact the circadian expression pattern of LIPE, which in turn may attenuate lipid mobilization and induce abdominal fat accumulation. Methods Abdominal adipose tissue explants from participants with obesity (n = 17) were cultured for a 24-h duration and analyzed every 4 h. Habitual nappers (n = 8) were selected to match non-nappers (n = 9) in age, sex, BMI, adiposity, and metabolic syndrome traits. Circadian LIPE expression rhythmicity was analyzed using the cosinor method. Results Adipose tissue explants exhibited robust circadian rhythms in LIPE expression in non-nappers. In contrast, nappers had a flattened rhythm. LIPE amplitude was decreased in nappers as compared with non-nappers (71% lower). The decrease in amplitude among nappers was related to the frequency of napping (times per week) where a lower rhythm amplitude was associated with a higher napping frequency (r = -0.80; P = 0.018). Confirmatory analyses in the activity of LIPE’s protein (i.e., HSL) also showed a significant rhythm in non-nappers, whereas significance in the activity of HSL was lost among nappers. Conclusion Our results suggest that nappers display dysregulated circadian LIPE expression as well as dysregulated circadian HSL activity, which may alter lipid mobilization and contribute to increased abdominal obesity in habitual nappers.